Individual strategies and release site features determine the extent of deviation in clock-shifted pigeons at familiar sites - Filannino, C; Armstrong, C; Guilford, T; Gagliardo, A (2014)
When homing from familiar areas, homing pigeons are able to exploit previously acquired topographical information, but the mechanisms behind this ability are still poorly understood. One possibility is that they recall the familiar release site topographical features in association with the home direction (site-specific compass orientation strategy), another that the spatial relationships among landmarks guide their route home (piloting strategy), without relying on the compass mechanism. The two strategies can be put in conflict by releasing clock-shifted birds at familiar locations, in order to highlight which is preferred. We analysed GPS tracks of clock-shifted pigeons, with familiarity controlled at each of three different release sites, and we observed that pigeons can display individual preferences for one of the two orientation strategies and that some characteristic features of the release site have an important role in determining the level of landmark-based homeward orientation. © 2013 Springer-Verlag Berlin Heidelberg.